Penentuan Tinggi Stemming Dan Jarak Burden Berdasarkan Jarak Flyrock Di Pit Inul Middle Panel 3 PT. Kaltim Prima Coal Kalimantan Timur - Yekeskiel Nimsi; Windhu Nugroho; Oktaviani, Revia (ReTII, 2023)
Stripping overburden using the blasting method is more economical than using equipment. One of the impacts caused by blasting activities is flyrock. Flyrock influences how far people and units have to be evacuated during blasting activities, so by controlling flyrock the evacuation distance can be reduced based on existing studies, in accordance with Ministerial Decree No. 1827.K/30/MEM/2018. By using the Richard and Moore equation, the distance of the flyrock throw can be predicted by approaching constant values ​​adjusted to the actual conditions at Pit Inul Middle. The research results show that there are several factors that influence the occurrence of flyrock, namely burden with a coefficient of determination value of 0.5183 and stemming height with a coefficient of determination value of 0.4142. Both of these factors have a moderate (medium or sufficient) correlation with flyrock. The actual average distance of flyrock that occurred during data collection was 11.58 meters and the furthest was 39.74 meters. By knowing the prediction of the maximum flyrock throw and considering the safety factor of the equipment, standard values ​​for the stemming and burden height variables can be set, namely a minimum of 2 meters.